Alternatives to inpatient mental health care for children and young people. - Shepperd, S; Doll, H; Gowers, S; James, A; Fazel, M; Fitzpatrick, R; Pollock, J (2009)
BACKGROUND: Current policy in the UK and elsewhere places emphasis on the provision of mental health services in the least restrictive setting, whilst also recognising that some children will require inpatient care. As a result, there are a range of mental health services to manage young people with serious mental health problems who are at risk of being admitted to an inpatient unit in community or outpatient settings. OBJECTIVES: 1. To assess the effectiveness, acceptability and cost of mental health services that provide an alternative to inpatient care for children and young people. 2. To identify the range and prevalence of different models of service that seek to avoid inpatient care for children and young people. SEARCH STRATEGY: Our search included the Cochrane Effective Practice and Organisation of Care Group Specialised Register (2007), the Cochrane Central Register of Controlled Trials (The Cochrane Library 2006, issue 4), MEDLINE (1966 to 2007), EMBASE (1982 to 2006), the British Nursing Index (1994 to 2006), RCN database (1985 to 1996), CINAHL (1982 to 2006) and PsycInfo (1972 to 2007). SELECTION CRITERIA: Randomised controlled trials of mental health services providing specialist care, beyond the scope of generic outpatient provision, as an alternative to inpatient mental health care, for children or adolescents aged from five to 18 years who have a serious mental health condition requiring specialist services beyond the capacity of generic outpatient provision. The control group received mental health services in an inpatient or equivalent setting. DATA COLLECTION AND ANALYSIS: Two authors independently extracted data and assessed study quality. We grouped studies according to the intervention type but did not pool data because of differences in the interventions and measures of outcome. Where data were available we calculated confidence intervals (CIs) for differences between groups at follow up. We also calculated standardised mean differences (SMDs) and 95% CIs for each outcome in terms of mean change from baseline to follow up using the follow-up SDs. We calculated SMDs (taking into account the direction of change and the scoring of each instrument) so that negative SMDs indicate results that favour treatment and positive SMDs favour the control group. MAIN RESULTS: We included seven randomised controlled trials (recruiting a total of 799 participants) evaluating four distinct models of care: multi-systemic therapy (MST) at home, specialist outpatient service, intensive home treatment and intensive home-based crisis intervention ('Homebuilders' model for crisis intervention). Young people receiving home-based MST experienced some improved functioning in terms of externalising symptoms and they spent fewer days out of school and out-of-home placement. At short term follow up the control group had a greater improvement in terms of adaptability and cohesion; this was not sustained at four months follow up. There were small, significant patient improvements reported in both groups in the trial evaluating the intensive home-based crisis intervention using the 'Homebuilders' model. No differences at follow up were reported in the two trials evaluating intensive home treatment, or in the trials evaluating specialist outpatient services. AUTHORS' CONCLUSIONS: The quality of the evidence base currently provides very little guidance for the development of services. If randomised controlled trials are not feasible then consideration should be given to alternative study designs, such as prospective systems of audit conducted across several centres, as this has the potential to improve the current level of evidence. These studies should include baseline measurement at admission along with demographic data, and outcomes measured using a few standardised robust instruments.